2010
DOI: 10.3174/ajnr.a1979
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Ablation of a Toxic Thyroid Nodule by High-Intensity Focused Ultrasound

Abstract: SUMMARY: HIFU is used in the treatment of cancer (prostate, breast) and uterine fibroma but not yet in TNs. This case report describes the first successful ablation of a toxic TN with HIFU. TSH and radioiodine scan normalization were achieved without complications and maintained for 18 months. HIFU treatment is a minimally invasive technique that may be an effective safe alternative to radioiodine or surgery in patients with toxic TNs.ABBREVIATIONS: AFTN ϭ autonomously functioning thyroid nodule; ENT ϭ ears, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Histological examination revealed that the damage was limited to the treated lesions with a nodule necrosis that ranged from 2 to 80 % [86]. A pilot study of a single hyperfunctioning nodule demonstrated that the nodule developed into a predominantly cystic lesion 2 weeks after treatment and that hyperthyroidism normalized after 3 months was maintained at 18 months [85]. The location of the nodule is important in determining the efficacy of HIFU.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Histological examination revealed that the damage was limited to the treated lesions with a nodule necrosis that ranged from 2 to 80 % [86]. A pilot study of a single hyperfunctioning nodule demonstrated that the nodule developed into a predominantly cystic lesion 2 weeks after treatment and that hyperthyroidism normalized after 3 months was maintained at 18 months [85]. The location of the nodule is important in determining the efficacy of HIFU.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…9,23,27,32 A case report on a single hyperfunctioning nodule demonstrated that 2 weeks after HIFU treatment, the nodule appearance was cystic at US. 33 Thyroid function normalized after 3 months and was maintained during the follow-up to 18 months. At US examination, the treated nodule appeared as a thin hypoechoic lesion devoid of vascular signals, and thyroid scintiscan showed functional recovery of the surrounding thyroid tissue.…”
Section: Clinical Efficacymentioning
confidence: 97%
“…Additional, but still inadequately investigated nonsurgical treatment options such as High Intensity Focused Ultrasound (HIFU) (57,122) and microwaves (58,123) are currently under evaluation. Although results are promising, they are too preliminary and sparse to allow any recommendations.…”
Section: Translating All the Aforementioned Into Clinical Practicementioning
confidence: 99%